Customer satisfaction measurement and management : using the voice of the customer - Naumann, Earl, 1946-; Giel, Kathleen (Cincinnati, Ohio : Thomson Executive Press, 1995)
This book is about: Commitment to customer satisfaction; Objectives and hypotheses; Research design; ...
Keywords: Management; Customer services; Customer services -- Management; Consumer satisfaction -- Evaluation